Physico-mechanical and biological properties of rubberwood particleboard bonded with citric acid - Rosli, Mohd Ashraaf (2019)
Particleboard is one the major timber products in Malaysia which generates the economy and exportation value. The usage of conventional synthetic resins would be restricted in the future due to depleting non-renewable fossil resources and the applications of renewable bio-based resins are therefore inevitable. Citric acid is one of a potential chemical that has good adhesion property for wood. The utilization of this chemical to replace urea formaldehyde resin in particleboard production could eliminate the problem of formaldehyde emission. The aim of this study is to determine the suitability of using citric acid to replace urea formaldehyde (UF) as binding agent in particleboard production. The performances of citric acid bondedparticleboard evaluated were physical, mechanical properties and its resistance against fungal decay and termite attacks. Particleboard bonded with citric acid met the standard requirement of water absorption, thickness swelling and internal bonding, however, the modulus of rupture (MOR) and modulus of elasticity (MOE) in static bending did not surpass the standard requirement. When compared to UF-bonded particleboard, the performance in terms of dimensional stability and mechanical properties of citric acid particleboard are significantly lower. As regards to biological properties, the citric acid-bonded boards had higher resistance towards white rot fungus and termites than urea-formaldehyde bonded boards.